UMP shares expertise in robotics literacy program in the UK - Nor Salwana, Mohammad Idris (UMPSA, 2023)
UNITED KINGDOM, May 18, 2023 - Universiti Malaysia Pahang (UMP) expands its reach by sharing its expertise in robotics literacy at the international level through the organization of the Robot Literacy Program with Community in Wales, Cardiff.